Blood neuro‐exosomal synaptic proteins predict Alzheimer's disease at the asymptomatic stage. Issue 1 (10th August 2020) - Jia, Longfei; Zhu, Min; Kong, Chaojun; Pang, Yana; Zhang, Heng; Qiu, Qiongqiong; Wei, Cuibai; Tang, Yi; Wang, Qi; Li, Ying; Li, Tingting; Li, Fangyu; et al.
Abstract: Introduction: Exosomes are an emerging candidate for biomarkers of Alzheimer's disease (AD). This study investigated whether exosomal synaptic proteins can predict AD at the asymptomatic stage. Methods: We conducted a two‐stage‐sectional study (discovery stage: AD, 28; amnestic mild cognitive impairment [aMCI], 25; controls, 29; validation stage: AD, 73; aMCI, 71; controls, 72), a study including preclinical AD (160) and controls (160), and a confirmation study in familial AD (mutation carriers: 59; non‐mutation carriers: 62). Results: The concentrations of growth associated protein 43 (GAP43), neurogranin, synaptosome associated protein 25 (SNAP25), and synaptotagmin 1 were lower in AD than in controls ( P < .001). Exosomal biomarker levels were correlated with those in cerebrospinal fluid (R 2 = 0.54–0.70). The combination of exosomal biomarkers detected AD 5 to 7 years before cognitive impairment (area under the curve = 0.87–0.89). Discussion: This study revealed that exosomal GAP43, neurogranin, SNAP25, and synaptotagmin 1 act as effective biomarkers for prediction of AD 5 to 7 years before cognitive impairment.